Pendred syndrome among patients with congenital hypothyroidism detected by neonatal screening: identification of two novel PDS/SLC26A4 mutations - Banghová, Karolína; Al Taji, Eva; Cinek, Ondřej; Novotná, Dana; Kremlíková Pourová, Radka; Zapletalová, Jiřina; Hníková, Olga; Lebl, Jan (European journal of pediatrics, 2008)
Pendred syndrome is an autosomal recessive disorder characterised by sensorineural hearing loss and thyroid dyshormonogenesis. It is caused by mutations in the PDS/SLC26A4 gene (OMIM 605646) encoding for pendrin. Hypothyroidism in Pendred syndrome can be--although rarely--present from birth and therefore diagnosed by neonatal screening. The aim of our study was to identify patients with Pendred syndrome among a historical cohort of patients with congenital hypothyroidism (CH) identified by neonatal screening, and to find their mutations in the PDS/SLC26A4 gene. We investigated 197 Czech Caucasian children with CH detected by the neonatal screening between the years 1985 and 2005. The clinical diagnosis of Pendred syndrome was based on the laboratory and sonographic signs of thyroid dyshormonogenesis in association with sensorineural hearing loss. In subjects clinically diagnosed with Pendred syndrome, we sequenced all exons and exon-intron boundaries of the PDS/SLC26A4 gene. Hearing loss was present in 10/197 children with screening-detected CH. Of these, three fulfilled the diagnostic criteria of Pendred syndrome. Two patients were compound heterozygotes for PDS/SLC26A4 mutations: patient 1 carried c.2089+1G>A / c.3G>C and patient 2 carried p.Tyr530His / p.Val422Asp. Two of the four identified mutations were novel (c.3G>C in patient 1 and p.Val422Asp in patient 2). The third patient was free of mutations in the PDS/SLC26A4 gene, representing a phenocopy. In conclusion, our results indicate the rarity of Pendred syndrome as a cause of CH. The identification of two novel mutations expands the spectrum of mutations in the PDS/SLC26A4 gene and emphasizes their marked allelic heterogeneity.
Keywords: Mutation; Child; percepční nedoslýchavost; novorozenec; Humans; lidé; mladiství; Congenital Hypothyroidism; Syndrome; Female; rodokmen; Male; Infant, Newborn; kongenitální hypotyreóza; mutace; Neonatal Screening; mužské pohlaví; ženské pohlaví; Anion Exchange Protein 1, Erythrocyte; Hearing Loss, Sensorineural; Pedigree; dítě; syndrom; novorozenecký screening; erytrocyty - protein 1 vyměňující anionty; Adolescent